Validation of the MCL35 gene expression proliferation assay in randomized trials of the European Mantle Cell Lymphoma Network. (10th August 2018) - Rauert‐Wunderlich, Hilka; Mottok, Anja; Scott, David W.; Rimsza, Lisa M.; Ott, German; Klapper, Wolfram; Unterhalt, Michael; Kluin‐Nelemans, Hanneke C.; Hermine, Olivier; Hartmann, Sylvia; Thorns, Christoph; Rymkiewicz, Grzegorz; et al.
Summary: Mantle cell lymphoma (MCL) is still considered incurable and the course of the disease is highly variable. Established risk factors include the Mantle Cell Lymphoma International Prognostic Index (MIPI) and the quantification of the proliferation rate of the tumour cells, e.g. by Ki‐67 immunohistochemistry. In this study, we aimed to validate the prognostic value of the gene expression‐based MCL35 proliferation assay in patient cohorts from randomized trials of the European Mantle Cell Lymphoma Network. Using this assay, we analysed the gene expression proliferation signature in routine diagnostic lymph node specimens from MCL Younger and MCL Elderly trial patients, and the calculated MCL35 score was used to assign MCL patients to low (61%), standard (27%) or high (12%) risk groups with significantly different outcomes. We confirm here in our prospective clinical trial cohort of MCL patients, that the MCL35 assay is strongly prognostic, providing additional information to the Ki‐67 index and the MIPI. Thus, this robust assay may assist in making treatment decisions or in devising risk‐adapted prospective clinical trials in the future.